Predictors of Sarcopenia in Outpatients with Post-Critical SARS-CoV2 Disease. Nutritional Ultrasound of Rectus Femoris Muscle, a Potential Tool - Cornejo Pareja, Isabel María; Soler-Beunza, Ana Gloria; Vegas-Aguilar, Isabel María; Fernández-Jiménez, Rocío; Tinahones-Madueño, Francisco José; García-Almeida, José Manuel (IOAP-MDPI, 2022)
Background and Objectives: The loss of muscle mass in post-critical COVID-19 outpatients is difficult to assess due to the limitations of techniques and the high prevalence of obesity. Ultrasound is an emerging technique for evaluating body composition. The aim is to evaluate sarcopenia and its risk factors, determining ultrasound usefulness as a potential tool for this purpose according to established techniques, such as the bioimpedance vector analysis (BIVA), handgrip strength, and timed up-and-go test. Methods: This is a transversal study of 30 post-critical COVID-19 outpatients. We evaluated nutritional status by ultrasound (Rectus Femoris-cross-sectional-area (RF-CSA), thickness, and subcutaneous-adipose-tissue), BIVA, handgrip strength, timed up-and-go test, and clinical variables during admission. Results: According to The European Society for Clinical Nutrition and Metabolism and the European Association for the Study of Obesity (ESPEN&EASO) Consensus for Sarcopenic and Obesity, in terms of excess fat mass and decreased lean mass, the prevalence of class-1 sarcopenic obesity was 23.4% (n = 7), and class-2 sarcopenic obesity was 33.3% (n = 10) in our study. A total of 46.7% (n = 14) of patients had a handgrip strength below the 10th percentile, and 30% (n = 9) achieved a time greater than 10s in the timed up-and-go test. There were strong correlations between the different techniques that evaluated the morphological (BIVA, Ultrasound) and functional measurements of muscle. Intensive care unit stay, mechanical ventilation, and age all conditioned the presence of sarcopenia in COVID-19 outpatients (R2 = 0.488, p = 0.002). Predictive models for sarcopenic diagnosis based on a skeletal muscle index estimation were established by RF-CSA (R2 0.792, standard error of estimate (SEE) 1.10, p < 0.001), muscle-thickness (R2 0.774, SEE 1.14, p < 0.001), and handgrip strength (R2 0.856, SEE 0.92, p < 0.001). RF-CSA/weight of 5.3 cm2/kg × 100 (...)
Keywords: COVID-19; Sarcopenia; Predictors of sarcopenia; Ultrasound of rectus femoris muscle; Post-critical SARS-CoV2 disease; COVID-19 survivors; Rectus femoris